Factors associated with delayed sputum smear conversion among Orang Asli with pulmonary tuberculosis in Malaysia from 2016 to 2020 - Ibrahim, Muhammad Naim (2021)
Background: Tuberculosis (TB) remains a challenge for public health worldwide. Enormous efforts have been made in fighting TB, but the outcome still below the expectation. The approach needs to be focused so that no one leaves behind, including vulnerable groups such as Orang Asli. Indigenous groups worldwide have a higher TB incidence and associated with delayed sputum smear conversion than the general population. There is a limited study to understand this situation among Orang Asli, hence dampening efforts in combatting TB among them. Objective: The current study aimed to measure the proportion of pulmonary TB, describe the characteristics of smear positive pulmonary TB and determine factors associated with delayed sputum smear conversion among Orang Asli in Malaysia from 2016 to 2020. Methodology: A retrospective cohort study was conducted in December 2020 until May 2021 utilised MyTB data. All registered TB among Orang Asli within the study period were included for the descriptive analysis. Then, the smear positive pulmonary TB was enrolled and followed until the end of the intensive phase. The estimated sample size needed was 445. Data on age, sex, tribes, location of residence, education level, household income, smoking status, diabetes mellitus, HIV status, BCG vaccination scar, treatment category, pre-treatment sputum smear, pre-treatment chest x-ray and treatment adherence were collected using the proforma and were analysed with SPSS ver. 26 software. A simple and multiple logistic regression was used to determine factors associated with delayed sputum smear conversion among Orang Asli. Results: There were 808 cases of Orang Asli in Malaysia from 2016 to 2020 diagnosed with TB. Out of 725 cases of pulmonary TB, 572 (78.9%) were smear positive pulmonary TB. Only 487 cases of smear positive pulmonary TB fulfilled the study criteria at the end of the intensive phase and included for further analysis. Of that, 93 (19.1%) cases were delayed sputum smear conversion. The mean (SD) age of smear positive pulmonary TB among Orang Asli was 39.20 (16.33) years, most were male (63%), Senoi tribe (54.9%), living in the rural area (88.1%), had formal education (60.4%) and living below the poverty line (97.1%). Factors significantly associated with delayed sputum smear conversion were smokers (AdjOR: 3.25; 95% CI: 1.88, 5.59), diabetes mellitus (AdjOR: 12.84; 95% CI: 6.33, 26.06), and HIV infection (AdjOR: 9.76; 95% CI: 3.01, 31.65). Conclusion: Pulmonary TB was the commonest type of TB reported among Orang Asli and are comparable to those of indigenous people worldwide. Targeted approaches and focused strategies towards pulmonary TB Orang Asli who are smokers, diabetic and HIV infection should be adopted by stakeholders to tackle delayed sputum smear conversion. With effective measures, the transmission of TB can be reduced, thus realising the End TB target.